2004
DOI: 10.1371/journal.pbio.0020042
|View full text |Cite
|
Sign up to set email alerts
|

Identifying Protein Function—A Call for Community Action

Abstract: Functional information is lacking for many of the hypothetical proteins encoded within sequenced genomes. Richard Roberts proposes that a community-based approach might offer an effecient way to fill the function gap

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
110
0

Year Published

2004
2004
2015
2015

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 126 publications
(112 citation statements)
references
References 4 publications
(4 reference statements)
2
110
0
Order By: Relevance
“…Since it is unrealistic to expect that all of these genes or even a signi®cant fraction of them will be studied experimentally any time soon, the functions of these genes need to be deduced through an integrative approach, combining high-throughput methods, computational analyses and curation (10).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Since it is unrealistic to expect that all of these genes or even a signi®cant fraction of them will be studied experimentally any time soon, the functions of these genes need to be deduced through an integrative approach, combining high-throughput methods, computational analyses and curation (10).…”
Section: Discussionmentioning
confidence: 99%
“…As the list of the`conserved hypothetical' proteins keeps growing at an escalating pace, integrative studies that combine protein and gene expression analyses, computational biology, comparative genomics, mutational analysis and curation can help in identifying the most intriguing genes in every genome (8,10). This in turn will create reasonable and veri®able hypotheses for further experimental and computational work towards better understanding of the functioning of (bacterial) cells.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As numerous studies have shown that the general paradigm is valid, however, our knowledge of the protein universe is less than perfect. Not only are the current annotations of protein-coding genes not comprehensive, but also a large proportion of genes in newly sequenced microbes and viruses cannot be annotated (or even identified; Roberts, 2004), which severely limits our ability to use metagenomics for microbial diversity studies. Although concerted efforts are under way to improve the coverage of known genome-derived proteins from wet-lab derived biochemical annotations, the technology to link the small body of experimentally generated evidence to large 'families' of similar proteins is still in flux.…”
Section: Better Bioinformaticsmentioning
confidence: 99%
“…Directed community approaches for systematic large-scale experimental protein characterization must follow, as has already been proposed and initiated for genome annotation and structural proteomics [71][72][73]. Without them, functional annotation of novel proteins or families by prediction alone is difficult.…”
Section: Unannotated Orfs: Technical Limits or Limited Knowledge?mentioning
confidence: 99%